게임플레이 가능성을 위한 감정요소 분석 프레임워크 - 김미진(Mijin Kim); 김재호(Jae Ho Kim) (한국콘텐츠학회 논문지, 10(6), 2010)
This study aims at empiricallly designing method to increase player's play capability through determining of the relations of player's behavior pattern and emotion factors when having gameplay experiences in MMORPG. For modeling emotion factors on gameplay, Our preliminary studies are considered in the process of rule-based systems on cognitive science approach. These study estabilished game architecture process applied of player's cognitieve emotion reactions in specific situation of role playing games that have most noticeable interaction with players based on quest system. This approach is expected to extend instant responses, which can be controlled behind all of anti-main behavior pattern and main behavior pattern in game playing. Therefore, such study is meaningful that is proposed the analysis framework of player's emotion factors to design game playing capability in game interactions. 본 논문은 MMORPG 게임플레이 경험에서 사용자의 행동패턴(Behavior Pattern)과 감정요소(Emotion Factors)간의 관계를 규명하여 사용자의 플레이 가능성(Play Capability)을 실증적으로 설계하기 위한 방법에 관한 것이다. 게임플레이 프로세스와 감정요소 도출을 모델링하기 위해 인지심리학적 측면(Process of Ruled-Based Systems on Cognitive Science Approach)에서 선행를 고찰하였다. 퀘스트(Quest)기반의 RPG게임내 특정상황에서 유저의 인지적 감정상태를 도출하기 위해 게임플레이 과정에서 생성되는 유저의 감정반응을 게임 설계과정에서 적용할 수 있는 프로세스를 정립하였다. 이러한 방법은 게임플레이 설계시 유저의 주류행동에 대한 통제 뿐만 아니라 비주류행동에 대한 감정상태의 실시간적 대응이 가능할 것으로 본다. 따라서 본 논문의 결과는 게임플레이 설계시 게임플레이 가능성을 향상시키기 위한 감정 분석 구조(Analytic Framework)를 제시함에 있어 의의를 갖는다.